2022
DOI: 10.3390/biom12010087
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Gene, and Hormonal Changes in Gonads and In-Creased Micrococcal Nuclease Accessibility of Sperm Chromatin Induced by Mercury

Abstract: Mercury is one of the most dangerous environmental pollutants. In this work, we analysed the effects of exposure of Mytilus galloprovincialis to 1, 10 and 100 pM HgCl2 for 24 h on the gonadal morphology and on the expression level of three stress genes: mt10, hsp70 and πgst. In this tissue we also evaluated the level of steroidogenic enzymes 3β-HSD and 17β-HSD and the expression of PL protein genes. Finally, we determined difference in sperm chromatin accessibility to micrococcal nuclease. We found alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Ingestion of pollutants such as MPs or most common heavy metals from contaminated food and water is the primary source of exposure to contaminants [44,45] that could induce severe damage to animal and human health [3,4]. Previous studies demonstrated that MPs could interact with intestinal cells [23,42]; for this reason, we decided to use two Furthermore, B2M was up-regulated at 24 and 48 h after exposure compared with controls (24 h vs. control group p-value = 0.0079; 48 h vs. control group p-value = 0.0088) (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingestion of pollutants such as MPs or most common heavy metals from contaminated food and water is the primary source of exposure to contaminants [44,45] that could induce severe damage to animal and human health [3,4]. Previous studies demonstrated that MPs could interact with intestinal cells [23,42]; for this reason, we decided to use two Furthermore, B2M was up-regulated at 24 and 48 h after exposure compared with controls (24 h vs. control group p-value = 0.0079; 48 h vs. control group p-value = 0.0088) (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of pollutants such as MPs or most common heavy metals from contaminated food and water is the primary source of exposure to contaminants [44,45] that could induce severe damage to animal and human health [3,4]. Previous studies demonstrated that MPs could interact with intestinal cells [23,42]; for this reason, we decided to use two immortalized intestinal epithelial cell lines from two different mammalian species.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic activities such as industry, urbanization, and land development (agricultural and mining) have serious effects on the environment, with constant intake of pollutants in terrestrial and marine compartment [ 1 , 2 , 3 , 4 ]. The heavy metals represent one of the most significant environment pollutants [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], and their negative effects on human and animal health are widely studied in the literature [ 6 , 7 , 12 , 13 , 14 ]. A major problem of heavy metals is their ability to bioaccumulate in the environment, animal, and plants and, through the food chain, to reach humans [ 12 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that reproduction is the basis of species survival, we investigated the possible effect of nickel on the reproductive health of one of the most-used organisms for the biomonitoring program, the Mediterranean mussel, M. galloprovincialis. M. galloprovincialis is an ideal model organism [ 5 , 35 , 36 , 37 ] because it is a filter-feeding sessile organism and accumulates different pollutants [ 7 , 36 ], such as heavy metals, hydrocarbons, and pesticides [ 5 , 7 ]. In addition, M. galloprovincialis is particularly abundant in the Mediterranean Sea [ 5 , 36 , 38 ] and thus represents an extremely important food source for populations living on the Mediterranean Sea coast [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation